An ESIPT-Based Fluorescent Probe for Aqueous Cu+ Detection through Strip, Nanofiber and Living Cells - Zhao Cheng; Xilang Jin; Yinggang Liu; Lei Zheng; Hao He (Molecules, 2023)
Constructed on the benzothiazole-oxanthracene structure, a fluorescent probe RBg for Cu+ was designed under the ESIPT mechanism and synthesized by incorporating amide bonds as the connecting group and glyoxal as the identifying group. Optical properties revealed a good sensitivity and a good linear relationship of the probe RBg with Cu+ in the concentration range of [Cu+] = 0–5.0 μmol L−1. Ion competition and fluorescence-pH/time stability experiments offered further possibilities for dynamic Cu+ detection in an aqueous environment. HRMS analysis revealed a possible 1:1 combination of RBg and Cu+. In addition, colorimetric Cu+ detection and lysosome-targeted properties of the probe RBg were analyzed through RBg-doped PVDF nanofiber/test strips and RBg-Mito/Lyso trackers that were co-stained in living HeLa cells, enabling the probe’s future applications as real-time detection methods for dynamic Cu+ tracking in the lysosomes and Cu+ detection under diversified conditions.